2009
DOI: 10.1124/jpet.109.155747
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation of Guinea Pig Intrinsic Cardiac Neurons by the PAC1 Agonists Maxadilan and Pituitary Adenylate Cyclase-Activating Polypeptide 27 (PACAP27)

Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP) evokes tachycardia followed by a larger cholinergic bradycardia in isolated guinea pig hearts. We used the selective PAC1 receptor agonist maxadilan and vasoactive intestinal polypeptide (VIP) to test the hypothesis that PACAP27-evoked tachycardia and bradycardia are mediated by VPAC and PAC1 receptors, respectively. Chronotropic actions of these peptides were evaluated in isolated perfused hearts. Direct neuronal actions were determined by intracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…In addition, PACAP regulates PAC1R expression [43,44], and absence of PACAP protein could be the reason for the differences in mRNA expression and protein levels between the arteries of WT and KO mice (and also for the different responses to PACAP1-38, but not to maxadilan). Hoover et al [45] showed that both maxadilan and PACAP1-27 activate PAC1R located on cardiac neurons; however, they differ in downstream signaling, indicating their importance. This suggests that PAC1R could be modified with its potency preserved.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PACAP regulates PAC1R expression [43,44], and absence of PACAP protein could be the reason for the differences in mRNA expression and protein levels between the arteries of WT and KO mice (and also for the different responses to PACAP1-38, but not to maxadilan). Hoover et al [45] showed that both maxadilan and PACAP1-27 activate PAC1R located on cardiac neurons; however, they differ in downstream signaling, indicating their importance. This suggests that PAC1R could be modified with its potency preserved.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, intravenous injection of PACAP in cat, sheep, and human provokes an increase in heart rate and enhances the contractile ventricular force (Minkes et al, 1992a;Sawangjaroen et al, 1992;Sawangjaroen and Curlewis, 1994;Birk et al, 2007). PACAP also caused bradycardia in isolated perfused guinea pig heart through both PAC1-R and VPAC-R (Chang et al, 2005;Hoover et al, 2009). In the anesthetized dog and on the isolated canine heart, PACAP evokes a transient positive followed by negative chronotropic and inotropic responses (Hirose et al, 1997b;Hirose et al, 1998).…”
Section: Pituitary Adenylate Cyclase-activating Polypeptidementioning
confidence: 99%
“…The PACAP peptide amino acid sequence is highly conserved, and the action of PACAP is tissue specific dependent on the activation of the different isoforms of the seven transmembrane G proteincoupled PACAP-selective PAC 1 receptor (Adcyap1r1) and/or the vasoactive intestinal peptide (VPAC) receptors (2,4,20,45,54). PACAP/PAC 1 receptor signaling modulates synaptic transmission and plasticity via pre-and postsynaptic mechanisms, and these effects have been shown to be critically important in central stress responses, peripheral sensory and autonomic function, and maintenance of physiological homeostasis (9,18,19,21,25,31,32,40,41,47,49,54).We previously identified colocalization of PACAP with acetylcholine in cholinergic parasympathetic preganglionic terminals innervating guinea pig cardiac neurons (5, 6) and demonstrated that both endogenously released and exogenously applied PACAP significantly increases cardiac neuron excitability through PAC 1 receptor activation (5,22,35,49). Cardiac neurons are more readily accessible than CNS neurons for experimental manipulations and accordingly, we have used these cells to further our understanding of cellular PAC 1 receptor signaling mechanisms.…”
mentioning
confidence: 96%